Hydroxylated derivatives of dimethoxy-1,4-benzoquinone as redox switchable earth-alkaline metal ligands and radical scavengers - Gulaboski, Rubin; Bogeski, Ivan; Mirčeski, Valentin; Saul, Stephanie; Pasieka, Bastian; Haeri, Haleh H; Stefova, Marina; Stanoeva, Jasmina Petreska; Mitrev, Saša; Hoth, Markus; Kappl, Reinhard (Springer Science and Business Media LLC, 2013)
Benzoquinones (BQ) have important functions in many biological processes. In alkaline environments, BQs can be hydroxylated at quinoid ring proton positions. Very little is known about the chemical reaction leading to these structural transformations as well as about the properties of the obtained hydroxyl benzoquinones. We analyzed the behavior of the naturally occurring 2,6-dimethoxy-1,4-benzoquinone under alkaline conditions and show that upon substitution of methoxy-groups, poly-hydroxyl-derivatives (OHBQ) are formed. The emerging compounds with one or several hydroxyl-substituents on single or fused quinone-rings exist in oxidized or reduced states and are very stable under physiological conditions. In comparison with the parent BQs, OHBQs are stronger radical scavengers and redox switchable earth-alkaline metal ligands. Considering that hydroxylated quinones appear as biosynthetic intermediates or as products of enzymatic reactions, and that BQs present in food or administered as drugs can be hydroxylated by enzymatic pathways, highlights their potential importance in biological systems.